KAJIAN UNIT PENANGKAPAN JARING KEMBUNG (GILLNET) DI TPI PANTAI LABU KABUPATEN DELI SERDANG The Study Units of Bloating Net (gillnet) in the Pumpkin TPI Deli Serdang Regency - Mas Bintang; Pindi Patana; Tajuddin Siregar (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Gillnet is a fishing gear for pelagic fishes as the fishing target. The research aimed to review unit bloating and analyze the composition, diversity, dominance, size and analysis of the economy. This research was conducted in Pumpkin TPI Deli Serdang Regency from August until December 2015. Result of the research found 3 species of fish those were Rastrellinger kanagurta as the mayor catch is 816.2 kg while the minor catches is Scomberomorus commerson as 65.1 kg and Selaroides leptolepis as 37.8 kg. During research, the value of diversity index both appliance catch have low between 0.182-0.355 while the value of dominance index high between 0.832-0.920. It indicate that selectivity both appliance catch’s high. The rate value at the appliance catch gillnet as the target catch is aqual to 40.81 kg/trip, higher from the sideline catch that is aqual to 5.145 kg/trip. Gillnet catch the fish with an average 58.44% competent minimum size. The effort analysis to value the Revenue-Cost Ratio (R/C) of 1.2 which means that the effort is worth doing and worth Payback Period (PP) of 0.8 years.Keywords: Gillnet, Composition of catches, The target catch, The sideline catch, Effort analysis